2021
DOI: 10.1523/eneuro.0567-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Local Connections of Pyramidal Neurons to Parvalbumin-Producing Interneurons in Motor-Associated Cortical Areas of Mice

Abstract: Acknowledgements: We would like to thank Editage (www.editage.com) for English language editing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 132 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…For postsynaptic CT neurons in layer 6 we used the same connection strengths as for layer 6 IT cells, 17 but reduced to 62% of original values, following published data on the circuitry of M1 CT neurons. 29 , 118 Our data 29 also suggested that connection strength from layer 4 to layer 2/3 IT cells was similar to that measured in S1, so for these projections we employed values from Lefort’s S1 connectivity strength matrix. 115 Experimentally, these connections were found to be four times stronger than in the opposite direction – from layer 2/3 to layer 4 – so we decreased the latter in the model to match this ratio.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…For postsynaptic CT neurons in layer 6 we used the same connection strengths as for layer 6 IT cells, 17 but reduced to 62% of original values, following published data on the circuitry of M1 CT neurons. 29 , 118 Our data 29 also suggested that connection strength from layer 4 to layer 2/3 IT cells was similar to that measured in S1, so for these projections we employed values from Lefort’s S1 connectivity strength matrix. 115 Experimentally, these connections were found to be four times stronger than in the opposite direction – from layer 2/3 to layer 4 – so we decreased the latter in the model to match this ratio.…”
Section: Methodsmentioning
confidence: 84%
“… 87 The model also accounts for layer 6 CT neurons generating relatively more inhibition than IT neurons. 29 , 118 Inhibitory connections from interneurons (PV and SOM) to other cell types were limited to neurons in the same layer, 116 with layers 4,5Aand 5B combined into a single layer. 77 Probability of connection decayed exponentially with the distance between the pre- and post-synaptic cell bodies with a length constant of 100 μm 66 , 67 .…”
Section: Methodsmentioning
confidence: 99%
“…For postsynaptic CT neurons in layer 6 we used the same connection strengths as for layer 6 IT cells, 17 but reduced to 62% of original values, following published data on the circuitry of M1 CT neurons. 29,118 Our data 29 also suggested that connection strength from layer 4 to layer 2/3 IT cells was similar to that measured in S1, so for these projections we employed values from Lefort's S1 connectivity strength matrix. 115 Experimentally, these connections were found to be four times stronger than in the opposite direction -from layer 2/3 to layer 4 -so we decreased the latter in the model to match this ratio.…”
Section: Local Connectivitymentioning
confidence: 84%
“…Forpostsynaptic IT and PT neurons with NCD between 0.37 and 0.8 (layers 5Aand 5B) we employed connectivity strength data from ( Anderson et al, 2010 ) with cortical depth resolution of 100 μm. For postsynaptic CT neurons in layer 6 we used the same connection strengths as for layer 6 IT cells ( Weiler et al, 2008 ), but reduced to 62% of original values, following published data on the circuitry of M1 CT neurons ( Yamawaki and Shepherd, 2015; Kuramoto et al, 2022 ). Our data ( Yamawaki and Shepherd, 2015 ) also suggested that connection strength from layer 4 to layer 2/3 IT cells was similar to that measured in S1, so for these projections we employed values from Lefort’s S1 connectivity strength matrix ( Lefort et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…We implemented the opposite pattern for excitatory connections arising from layer 4,5A,5B IT cells such that PV interneurons received stronger intralaminar inputs than SOM cells ( Apicella et al, 2012 ). The model also accounts for layer 6 CT neurons generating relatively more inhibition than IT neurons ( Yamawaki and Shepherd, 2015; Kuramoto et al, 2022 ). Inhibitory connections from interneurons (PV and SOM) to other cell types were limited to neurons in the same layer ( Katzel et al, 2011 ), with layers 4, 5A and 5B combined into a single layer ( Naka and Adesnik, 2016 ).…”
Section: Methodsmentioning
confidence: 99%